Analisis Strategi Komunikasi Pengguna Media Sosial Instagram Non-Celebrity dalam Membentuk Personal Branding - Hayati, Kumala; Saraswati, Dini Putri (Avant Garde, 2023)
Long before the advent of the internet, conventional media was the only medium that could be used to reach audiences. Only related parties such as celebrities have access to connect themselves with the public. But since the internet gave birth to derivative products such as the social media Instagram, all parties have the same access to connect with each other, including non-celebrities. They are free to determine the purpose of using Instagram. One of them is forming personal branding. Of course, this requires the right communication strategy to attract the attention of other users, especially considering the large number of Indonesians who join Instagram. This research wants to analyze how the general public in Indonesia uses their Instagram accounts to form personal branding. The theory used is Rampeshad's personal branding strategy. The research method used is a qualitative descriptive with interview and observation data collection techniques through content analysis techniques on users' Instagram accounts. The results indicate that there are three communication strategies to form personal branding used by informants: through niches that are formed according to the values and vision to be conveyed and describe the characteristics of the individual; consistency through kitsch; and message preparation to gain credibility from followers and optimization. Instagram features.